An exploration of instructional behaviors of a teacher in a mobile learning context. (January 2023) - Liu, Ching-Leng; Lai, Chiu-Lin
Abstract: Mobile learning has been frequently adopted, but it is necessary to explore how teachers face the challenges. In this study, an experienced teacher's teaching behaviors were collected and analyzed through sequential pattern analysis. Also, an interview with the teacher was conducted. The result showed that the teacher put a great deal of effort into creating a positive learning atmosphere. His teaching behavioral pattern in mobile learning was more scattered than that in conventional teaching mode. This might be the biggest challenge for novice teachers. Finally, this study found that the students' basic digital skills were also a vital element. Highlights: A teacher's teaching behaviours in mobile learning context was explored. The teacher performed different behaviours in different teaching modes. The teacher made an effort to create a positive learning atmosphere. The teaching behaviours was more scattered than that in conventional teaching mode. The students' digital skills were a vital element in successful mobile learning.